(untitled) (Herald of Journalism, 2019)
This day simple paper and pen have already changed by new technologies and computer programs and could not be used as before. Day by day, digital programs are becoming more and more important for improvement of work in government organizations and to increase a media literacy among population. Therefore, this article is going to talk more about it. Given article has main aim like a comparative analysis of Kazakh and foreign organizations’ web-programs and its advantages and disadvantages, effectiveness and working system that used in service centers and higher education institutions. Applying computer nets and mobile services like EGOV and Unver is important not only to enlarge a quality of service labor and time-economy, but also it has a vital role for service-users too. People have good opportunity to observe the process and prove their capacity in using modern technologies and media literacy. It plays as a role in providing new program ‘Digital Ka-zakhstan-2020` in the Republic of Kazakhstan and noticeable sample of e-government. Whilst scientific research these advantages would be investigated and made a bright definition to population. Kazakh web-programs were explored in compare with foreign experiences and prototypes based on analysis In the process of writing article. Moreover, there are researches about different programs of organizations and its disadvantages.